GmWRKY49, a Salt-Responsive Nuclear Protein, Improved Root Length and Governed Better Salinity Tolerance in Transgenic Arabidopsis - Xu, Zhaolong; Raza, Qasim; Xu, Ling; He, Xiaolan; Huang, Yihong; Yi, Jinxin; Zhang, Dayong; Shao, Hong-Bo; Ma, Hongxiang; Ali, Zulfiqar (Frontiers in Plant Science, 2018)
Plant WRKY transcription factors are active guardians against pathogens insurgency, key components in developmental processes, contributors in signal transduction pathways and regulators of diverse biotic and abiotic stress responses. In this research, we isolated, cloned and functionally characterized a new WRKY transcription factor GmWRKY49 from soybean. GmWRKY49 is a nuclear protein which contains two highly conserved WRKY domains and a C2H2 type zinc-finger structure. The normalized expression (log2 ratio) of GmWRKY49 was 2.75-fold and 1.90-fold in salt tolerant and salt susceptible soybean genotypes, respectively. The transcripts of GmWRKY49 could be detected in roots, stems, leaves, flowers, almost no expression in pod tissues. The salinity tolerance response of this gene was studied through overexpression in soybean composite seedlings and transgenic Arabidopsis. The effect of GmWRKY49-overexpression on root length of transgenic Arabidopsis was also investigated. Under salt stress, several parameters including germination rate, survival rate, root length, rosette diameter, relative electrolyte leakage and proline content were significantly higher in composite seedlings and transgenic Arabidopsis than those in wild-type. Moreover, GmWRKY49 enhanced salinity tolerance in soybean mosaic seedlings and transgenic Arabidopsis. These results suggest that GmWRKY49 is a positive regulator of salinity tolerance in soybean and has high potential utilization for crop improvement.